Coupled–Channels Analyses For Heavy–Ion Fusion Reactions of 16O+92Zr,144,148Sm Systems - M. Zamrun; K. Hagino (PPIKSN-BATAN, 2010)
We study in detail the fusion reaction of 16O with 92Zr and 144,148Sm at sub-barrier energies with coupled-channels framework using the error function potential for the nuclear potential. In particular, we investigate the effects of multiphonon excitations in target nuclei on experimental fusion cross section and barrier distributions for these reactions. We show that the present coupled-channels calculations well account for the experimental data of the fusion cross section as well as the fusion barrier distributions. It is shown that the coupled-channels calculations taking into account the coupling up to double quadrupole phonon excitations in 92Zr well reproduce the experimental fusion cross section as well as fusion barrier distribution for 16O+92Zr. However, for 16O+144Sm, coupling to single quadrupole and octupole phonon states in 144Sm can well explain the experimental data. And the coupling up to triple quadrupole phonon states and double octupole phonon excitations in 144Sm are needed in order to reproduce the experimental data. Our study indicates the error function potential is adequate for analyses of the heavy-ion fusion reactions. Received: 20 November 2009; Revised: 17 April 2010; Accepted: 18 April 2010